The Theory of Critical Distances as an alternative experimental strategy for the determination of KIc and ΔKth - TAYLOR, DAVID (My University, 2010)
The present technical note is concerned with the use of the Theory of Critical Distances, applied in the form of the Point Method, to estimate the range of the threshold value of the stress intensity factor, ?Kth, as well as the plane strain fracture toughness, KIc, of conventional engineering materials. In more detail, it is shown that ?Kth can efficiently be evaluated by measuring two fatigue limits: the fatigue limit plain (unnotched) specimens and a second fatigue limit generated by testing samples containing a stress concentration feature such as a notch. The KIc, on the other hand, can be accuractely estimated by using experimental results obtained by testing samples containing notches of two different sharpnesses. The accuracy and reliability of the proposed experimental methodology was checked by using a large amount of experimental results taken from the literature. Such a systematic validation exercise allowed us to fully confirm that the Theory of Critical Distances is not only an accurate static and fatigue assessment technique, but it can also be considered as an efficient experimental strategy suitable for estimating the classical Linear Elastic Fracture Mechanics material properties.
PUBLISHED
Keywords: Theory of Critical Distances